Classification of Bleeding Events: Comparison of ECASS III (European Cooperative Acute Stroke Study) and the New Heidelberg Bleeding Classification. Issue 7 (July 2017) - Neuberger, Ulf; Möhlenbruch, Markus Alfred; Herweh, Christian; Ulfert, Christian; Bendszus, Martin; Pfaff, Johannes
Abstract : Background and Purpose—: Intracranial hemorrhage (ICH) after acute ischemic stroke treatments represents a feared complication with possible prognostic implications. In recent years, ICHs were commonly classified according to the ECASS (European Cooperative Acute Stroke Study). To improve the clinical applicability and relevance, the new Heidelberg Bleeding Classification (HBC) has been proposed in 2015. Here, we compared the ECASS and HBC classification with regard to observed events and prognostic relevance. Methods—: A retrospective analysis of a prospectively compiled database of patients with acute ischemic stroke in the anterior circulation who received mechanical thrombectomy between February 2011 and March 2016 was performed. Presence of ICH after mechanical thrombectomy was evaluated on postinterventional computed tomographic imaging. ICHs were specified according to both ECASS III and HBC classification and analyzed with regard to their symptoms and outcome. Results—: ICHs were observed in 156 of 768 patients (20.3%). Using ECASS III classification, 101 ICHs could be unambiguously assigned, of which 28 (27.7%; 3.6% of all treated patients) were symptomatic ICHs. Using HBC, 55 additional ICHs could be categorized. Of these total 156 ICHs, 29 (18.6%; 3.8% of all treated patients) were classified as symptomatic according to HBC. Conclusions—: Classification of ICH by ECASS III and HBC criteria show distinct differences. These differences warrant special attention during interpretation and comparison of scientific publications. Abstract : Supplemental Digital Content is available in the text.